In vitro and in vivo studies on pre-mRNA splicing in plants - Albaqami, Mohammed M., author; Reddy, A. S. N., advisor; Wilusz, Jeffrey, committee member; Ben-Hur, Asa, committee member; Montgomery, Tai, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.